Red blood cell membrane deformability in hemodialysed children - Böhler, Thomas; Leo, Albrecht; Schärer, Karl; Linderkamp, Otwin (Clinical hemorheology and microcirculation, 1993)
Red blood cell (RBC) deformability was studied by means of a rheoscope and RBC membrane rigidity (i.e. membrane extensional elastic modulus, μe ) was measured by using a flow channel in seven children and adolescents (9 to 17 years) with chronic rena
Gesehen am 17.02.2021